Implementation of green infrastructure as stormwater management in Portland, Oregon - Kulkarni, Madhuri (Kansas State University, 2012)
Green infrastructure is an emerging concept which utilizes vegetated systems rather than traditional gray infrastructure for stormwater management. Conducting a literature review revealed the effectiveness of incentive based planning, the benefits of green infrastructure, information on bioswales and wetlands, stormwater management, Portland, and planning implementation strategies. Portland, Oregon, was selected as the area of study because of its widespread application of green infrastructure. Seeking to understand the reasoning behind the implementation of this atypical civic infrastructure, existing policies in the city’s Comprehensive Plan and the Zoning Code were analyzed. A policy analysis was conducted through itemizing the relevant policies in the Comprehensive Plan and the Zoning Code. Additionally, six in-depth phone interviews were conducted with Portland base planning-related professionals utilizing a snowball sampling technique to qualitatively understand the policies and circumstances that enabled the implementation of the city’s bioswales and wetlands. Findings were revealed through using the grounded theory methodology of coding and memoing to analyze the responses from the interviews. According to the policy itemization and phone interviews, the Comprehensive Plan and Zoning Code were not the reasons for Portland’s green infrastructure implementation, as hypothesized. Instead, green infrastructure was evident due to a need for compliance with the U.S Environmental Protection Agency’s Clean Water Act, and a resulting Stormwater Management Manual created by the city. Additionally, other reasons for implementation included strong leaders, active citizens, and incentives and grants. The city encountered several challenges with implementation including costs, a technical lack of information, and opposition from members against using green infrastructure, which were all ultimately overcome. Lessons learned from this case study of Portland point to four policy recommendations for other cities wanting to implement green infrastructure to help alleviate pollution and flooding: the need for design having a general Comprehensive Plan and detailed Stormwater Management Manual, experimentation to generate and monitor data, collaboration, and funding.
Keywords: Stormwater management; Green infrastructure; Portland; Implementation; Bioswales; Sustainability; Urban Planning (0999)